On the Electronic Structure of mer, trans‐[RuCl3(1H‐indazole)2(NO)], a Hypothetical Metabolite of the Antitumor Drug Candidate KP1019: An Experimental and DFT Study. Issue 14 (4th April 2013) - Bučinský, Lukas; Büchel, Gabriel E.; Ponec, Robert; Rapta, Peter; Breza, Martin; Kožíšek, Jozef; Gall, Marian; Biskupič, Stanislav; Fronc, Marek; Schiessl, Katharina; Cuzan, Olesea; Prodius, Denis; et al.
Abstract: The study reported herein focused on the electronic structure of the {Ru(NO)} 6 fragment and characterization of the oxidation state of ruthenium in mer, trans ‐[RuCl3 (Hind)2 (NO)] (1 ; Hind = 1 H ‐indazole) resulting from the reaction of mer, trans ‐[RuCl3 (H2 O)(Hind)2 ] (2 ) with NO in acetone or solid‐state Anderson rearrangement of (H2 ind)2 [RuCl5 (NO)] at 180 °C. The results of X‐ray diffraction, 1 H, 13 C, and 15 N NMR, EPR, IR, and UV/Vis spectroscopy, cyclic voltammetry, magnetic susceptibility, and XANES/EXAFS as well as theoretical data have been critically analyzed. The localized orbitals, domain‐averaged Fermi holes, frontier orbitals, Mulliken population, and quantum theory of atoms‐in‐molecules (QTAIM) analyses are presented. In addition, mer, trans ‐[Ru III Cl3 (H2 O)(Hind)2 ] (2 ) and trans ‐[Ru II Cl2 (Hind)4 ] (3 ) were experimentally and theoretically investigated as reference compounds. A complete active space SCF calculation was performed to estimate the extent of antiferromagnetic spin–spin coupling in1 . We found that the closed‐shell structure {Ru III (NO) 0 } 6 fits better to the physical/spectroscopic properties of1, although {Ru II (NO) + } 6 is formally still suitable for describing the oxidation state of Ru in this entity. Abstract : The electronic structure of the {Ru(NO)} 6 fragment and the characterization of the oxidation state of ruthenium in mer, trans ‐[RuCl3 (indazole)2 (NO)] by X‐ray diffraction, 1 H, 13 C, and 15 N NMR, EPR, IR, and UV/Vis spectroscopy, cyclic voltammetry, magnetic susceptibility, and XANES/EXAFS as well as by theoretical DFT calculations are reported.